Analisis Faktor – Faktor yang Mempengaruhi Kecurangan Laporan Keuangan dengan Perspektif Fraud Diamond - Devitasari Nurani Pratiwi; Yunus Tete Konde; Muhammad Subhan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
This study was conducted to analyze the effect of the Development variables of fraud triangle by Cressey, the fraud diamond proposed by Wolfe and Hermanson (2009) that financial targets, financial stability, external pressure, nature of industry, ineffective monitoring, change in auditors, rationalization and capability towards the financial statement fraud which proxied by earnings management. The samples used in this study are 53 manufactured company that listed in Indonesia Stock Exchange during the period 2012-2014. The type of data used are secondary data, in the form of annual reports of companies listed on the Stock Exchange during the period 2012-2014. Hypothesis testing was conducted using multiple linear regression with SPSS 20 software. The results showed that the variables of financial stability which proxied by change in total assets ratio, external pressure variables which proxied by leverage ratio, financial targets variables which proxied by ROA (Return On Asset), and nature of the industry which is proxied by the change in receivables ratio shown to affect the financial statement fraud. This study does not prove that personal financial need which proxied by OSHIP, ineffective monitoring variable which proxied by the ratio of audit committee board independent, rationalization which proxied by change in auditors, and capability which is proxied by the change of directors has an influence on the financial statement fraud.Keywords: Fraud Triangle, SAS 99, Fraud Diamond, Financial Statement Fraud.